Rising Food Prices and Coping Strategies : Household-level Evidence from Afghanistan - D’Souza, Anna (Taylor and Francis, 2013)
This article investigates the impact of rising wheat prices on household food security in Afghanistan. Exploiting a unique nationally-representative household survey, we find evidence of large declines in the real value of per capita food consumption. Smaller price elasticities with respect to calories than with respect to food consumption suggest that households trade off quality for quantity as they move away from nutrient-rich foods such as meat and vegetables toward staple foods. Our work improves upon country-level simulation studies by providing estimates of actual household food security during a price shock in one of the world's poorest, most food-insecure countries.